PERAN DINAS PENDIDIKAN KOTA PEKANBARU DALAM MEWUJUDKAN AKSES PENDIDIKAN YANG MERATA DAN BERMUTU TAHUN 2018 - Reza Pradana Nugraha; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Education is something that is very essential in the humanitarian process in a cultured society. So in practice, every child has the right to get an education which has become his right to obtain an education that is accessible and of good quality. There are various kinds of problems to make it happen, such as education infrastructure such as school spaces that are still lacking, and the low quality of education is caused by the number of teachers who are not evenly distributed and the level of teacher welfare cannot be said to be good, especially teachers who are not civil servants. There are two problem formulations in this research, namely